Assuming this is part of an equation but missing "= 0" and you want the values of y: (3y - 3)(y - 2) are the factors so y = 1 or 2.
If ' y ' is greater than ' 1 ', then [ 3y to the second power ] is. If ' y ' is less than ' 1 ', then 3 is.
81y4
This is like a² - b², with a = 9x² and b = 9y². This can be factored as (a - b)(a + b), then substitute for a & b: (9x² - 9y²)(9x² + 9y²), then (9x² - 9y²) can factor to (3x - 3y)(3x + 3y) so we have: (3x - 3y)(3x + 3y)(9x² + 9y²)
x = 3y x - 3y = 3y - 3y x - 3y = 3y - 3y x - 3y = 0
I'm not sure why this is labeled as calculus; it's just algebra. You take the first coefficient and the 2nd coefficient and add them. 1y x 3y = (1+3)y = 4y
Assuming this is part of an equation but missing "= 0" and you want the values of y: (3y - 3)(y - 2) are the factors so y = 1 or 2.
If ' y ' is greater than ' 1 ', then [ 3y to the second power ] is. If ' y ' is less than ' 1 ', then 3 is.
34
81y4
(3y2)4*3y2*3y2*3y2*3y2 = 38*y16 = 6561y16
Factor it. y(4y - 1)(3y - 2) = 0 y = 0, 1/4, 2/3
25
This is like a² - b², with a = 9x² and b = 9y². This can be factored as (a - b)(a + b), then substitute for a & b: (9x² - 9y²)(9x² + 9y²), then (9x² - 9y²) can factor to (3x - 3y)(3x + 3y) so we have: (3x - 3y)(3x + 3y)(9x² + 9y²)
x = 3y x - 3y = 3y - 3y x - 3y = 3y - 3y x - 3y = 0
6xy(2x2 - 3y)
2y2(3y - 1)